The Impact of Corporate Governance on Financial Performance of Indonesian Banks - Aganeka Pratama; Muhamad Iqbal; Farah Margaretha Leon (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study analyzes the influence of board size, managerial ownership, ownership concentration, firm age, leverage, and firm size on financial performance, measured by Return on Assets (ROA). The research utilizes data from banking sub-industry companies listed on the Indonesia Stock Exchange during the 2019–2024, with 110 samples obtained through purposive sampling techniques. The study employs a quantitative approach using multiple linear regression analysis with Eviews. The findings reveal that board size negatively affects financial performance, while managerial ownership, ownership concentration, company size, leverage, and company age positively influence financial performance. These results suggest that management should focus on factors that enhance financial performance to improve company profitability, while investors can use these insights to identify promising companies for investment. Future research is encouraged to incorporate corporate governance variables, such as audit committee size, and to expand the scope to other sectors and longer study periods.